Islamic Spiritual Wellbeing among Elders - Minarti Minarti; Kastubi Kastubi (Alliance of Health Activists (AloHA), 2019)
Aging among elders creates various problems, including health issues. Fulfilling spiritual wellbeing is important in both sickness and healthy conditions. Continual spiritual distress influence health status of elders including decrease on eating, sleeping disorder, and increase on blood pressure. This study aims to investigate Islamic spiritual wellbeing among elder in Posyandu around Surabaya. It specifically identifies Islamic spiritual wellbeing based on repentance, patience, submission, and contentment. It is a descriptive study recruiting 45 elders population and purposively selected 43 among them as samples. The study reveals that 90.70% of the elders experience a high quality of spiritual wellbeing. Repentance reaches 88.37%, contentment (86.05%), submission (66.77%) and patience (67.44%). This study recommends that elders need to maintain and increase their spiritual wellbeing. Keywords: Islamic, Spiritual Wellbeing, Elders